2017
DOI: 10.2527/jas2017.1864
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structured antedependence and random regression models applied to the longitudinal feed conversion ratio in growing Large White pigs1

Abstract: The objective of the present study was to compare a random regression model, usually used in genetic analyses of longitudinal data, with the structured antedependence (SAD) model to study the longitudinal feed conversion ratio (FCR) in growing Large White pigs and to propose criteria for animal selection when used for genetic evaluation. The study was based on data from 11,790 weekly FCR measures collected on 1,186 Large White male growing pigs. Random regression (RR) using orthogonal polynomial Legendre and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…Instead, animals should be selected based on the trajectory of their TEBV over time. This selection requires a limited number of descriptive parameters of these trajectories, which are usually obtained by eigendecomposition of the genetic covariance matrix [ 15 , 30 ]. It has been shown that the two first eigenvectors obtained with longitudinal models are usually sufficient to describe the trajectory of feed efficiency [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Instead, animals should be selected based on the trajectory of their TEBV over time. This selection requires a limited number of descriptive parameters of these trajectories, which are usually obtained by eigendecomposition of the genetic covariance matrix [ 15 , 30 ]. It has been shown that the two first eigenvectors obtained with longitudinal models are usually sufficient to describe the trajectory of feed efficiency [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…This selection requires a limited number of descriptive parameters of these trajectories, which are usually obtained by eigendecomposition of the genetic covariance matrix [ 15 , 30 ]. It has been shown that the two first eigenvectors obtained with longitudinal models are usually sufficient to describe the trajectory of feed efficiency [ 15 ]. The corresponding summarised estimated breeding values (SBV1 and SBV2), which are the product of the vector of TEBV with the first or the second eigenvectors, generally correspond to the EBV for average feed efficiency and the EBV for the main slope of the trajectory over time, respectively [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The popularity of RRM has increased substantially in animal breeding research over the past years, and RRM have been considered the method of choice to genetically evaluate longitudinal traits in various livestock species, including dairy cattle (e.g., Kheirabadi, 2018;Padilha et al, 2018), beef cattle (e.g., Oliveira et al, 2018a), sheep (e.g., Saghi et al, 2018), goats (e.g., Brito et al, 2018), horses (e.g., Bartolomé et al, 2018), swine (e.g., Huynh-Tran et al, 2017), poultry (e.g., Miyumo et al, 2018), quail (e.g., Mota et al, 2018a), and fish (e.g., Zhao et al, 2018).…”
Section: Applications Of Rrmmentioning
confidence: 99%